VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Sports and Medicine (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-041 Efficacy of rehabilitation in soccer players undergoing ACL repair using hamstring tendon grafting P-042 Relationship of daily changes in salivary secretory immunoglobulin a and appearance of upper respiratory symptoms during soccer training P-043 Effects of leisure exercise on blood paraoxonase and arylestarese activities and relationship with paraoxonase 1-192 polimorphism P-044 Relationship between potassium and free radicals in a soccer competition half-season P-045 Laboratory and on the field follow up of training process of professional soccer players using blood lactates